PENERAPAN METODE KAISA PADA PENGHAFAL SURAH-SURAH PENDEK PADA ANAK USIA DINI DI TK BUNDA ISNAINI MAWARDI MEDAN - Yuli Anisah Hasibuan; Dedi Masri; Afrah Nadhilah Hasibuan; Eka Riski Pitriana (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2023)
Summary: : Is Talaqi not interested enough Student because Impressed Boring And Easy to lost Method kingdom? The Method Currently Learned Must Be Adapted With Aim Which Is Desired Method Which Related Wite Al-Qur'an Kindly Special Rote Present As A Solution Since This Method Not Only Gives Understanding Or Just Speaks Text, But Also Uses Action That Proceeds And Given Name With Read Means Simplex Which Actually Thing This Make. Once more students, simply remember that the goal of learning this is for full application. For kindergarten, Kaisa ISNAINI MAWARDI, MOTHER Learn How To Get Information Using A Qualitative Approach. By Element In Application Approach Imperial On Al-Qur'anic Type Of Ingredient. Study This Including In Category Studies Case, that is, Study This Show Case genuine in present context. Kaisa Will Use This Method. BUNDA ISNAI MAWARDI use software in.TK to arrange the syllabus. Using empirical methods, RPP uses the Kaisa method for process learning and performs an evaluation for subsequent repair learning. Support consists of encouraging students to learn, creating a pleasurable learning environment, and addressing any barriers to learning, such as the need for preparation and students' inresidence Yangs' lack of understanding of some imperial methods